Pisciculture with pond dikes’ utilization for additional income and employment in Tripura - Debnath, Chandan (Indian Farming, 2024)
Pisciculture is an important agri-allied sector in Tripura, Northeast India. Presently, more than 2.1 lakh people are associated with this sector for food and livelihood security. However, the majority of these people (94%) fall under the category of marginal and small farmers, with an average pond holding of less than 0.10 ha (locally known as 1 kani) and an income of `7500-37500/ha/year, which is meager compared to the actual potential of science-led pisciculture. Composite fish culture (CFC) is a proven technology, but it is highly capital-intensive, and poor farmers find it difficult to afford in their ponds. Further, most of the ponds are small and seasonal which is unfit for CFC. In this situation, modifying it according to farming conditions, and additionally integrating them with pond dikes for additional income, can bring about significant changes in pond-dependent livelihoods in Tripura, in general, and Northeast India, in particular. Through appropriate pisciculture interventions, it is possible to derive an annual net income of `40,000-510,000 from a 1-hectare pond and additionally `60,000-89,450 through the utilization of its dikes for different agri-horti crops, besides generating 150-200 additional man-days year-round. Hence, pisciculture with pond dike utilization techniques is highly recommended in settings where farmers have very limited resources.